Bulk industrial fruit fibres. Characterization and prevalence of the original fruit metabolites. (September 2018) - Delpino-Rius, Antoni; Marsol-Vall, Alexis; Eras, Jordi; Llovera, Montse; Cubero, Miguel Ángel; Balcells, Mercè; Canela-Garayoa, Ramon
Abstract: Here we analysed the content of primary and secondary metabolites in nine types of industrially processed fibres derived from the juice industry. Specifically, we examined fibre from: apple, peach, and pear, as non-citrus fruits; the peel and flesh of orange and tangerine, and lemon flesh, as citrus fruits; and carrot, as vegetable. Regarding primary metabolites, the sugar content ranged from 21.6 mg/g in lemon to 290 mg/g in orange peel and lower mass organic acid content ranged from 25.0 mg/g in pear to 250 mg/g in lemon. The content of fatty acids were constant during fibre processing, ranging from 0.5 to 1.46%. Furthermore, the fatty acid profile was not affect for the processing. Concerning secondary metabolites, industrial processing did not decrease the sterols content, which ranged from 0.51 to 1.66 μg/g. Regarding carotenoids, of note was the presence of epoxycarotenoids, which may reflect the quality of the industrial process, thus giving added value to the by-product. Graphical abstract: Unlabelled Image Highlights: Primary and secondary metabolites were analysed in fibres from juice industry. The fibres contained significant amounts of sugars and organic acids. Ursolic and oleanolic acids are bioactive compounds found in apple fibres. Epoxycarotenoids were found in fibres from juice industry.